II. ABDÜLHAMİD DÖNEMİNDE ZİRAİ EĞİTİMHAMLESİ: HÜDAVENDİGAR HAMİDİYE ZİRAATAMELİYAT MEKTEBİ VE NUMUNE ÇİFTLİĞİ (1891-1909 - (:unkn) unknown (My University, 2021)
II. Abdülhamid döneminde eğitimin modernleştirilmesi doğrultusunda pekçok gelişme yaşanmıştır. İlk, orta ve yükseköğretimde olduğu gibi mesleki veteknik eğitim alanında da yeni eğitim kurumları tesis edilmiştir. Özelliklemesleki eğitimde, ülkenin içinde bulunduğu sosyo-ekonomik durum dikkatealınarak adım atılmaya çalışılmıştır. Bu konuda en temel örneklerden biriniziraat meselesi ve ziraat mektepleri oluşturur. II. Abdülhamid iktidarageldikten sonra ziraat alanında modernleşme ve ziraat eğitimi gündemegelmiş ve Halkalı’da bir ziraat mektebi tesisine girişilerek uzun ömürlü ilkadım atılmıştır. Ziraat Mektepleri sadece İstanbul ile sınırlı kalmamış,vilayetlerde de tesis edilmiştir. İşte bu çalışmada, II. Abdülhamid dönemieğitim politikaları ve ziraat anlayışı doğrultusunda Bursa’da açılanHüdavendigar Ziraat Ameliyat Mektebi ve Numune Çiftliği ele alınmıştır. Bubağlamda, mektebin açılış süreci, idari ve öğretim kadrosu, müfredat vedersler, imtihanlar, öğrenci sayısı, mezuniyet, mektebin sosyal durumu ileçiftlik hakkında ayrıntılı bilgiler verilmiştir. Bursa’daki Ziraat Mektebi,döneminde Halkalı ve Selanik Ziraat Mektepleri ile birlikte, OsmanlıDevletinde modern ziraat eğitiminin verildiği üç eğitim kurumundan biridir.Akabinde Meşrutiyet ve Cumhuriyet Türkiye’sinde varlığını devam ettiren buokul, günümüzde II. Abdülhamid döneminde inşa edilen ziraatmekteplerinden tarihi misyonunu devam ettiren tek okul olma özelliğiyle,Türk eğitim tarihinde ayrı bir yere sahiptir.

During the reign of Abdülhamid II, there have been many developments to modernize education. As in primary, secondary, and higher education, new educational institutions were established in the field of vocational and technical education. Especially in vocational education, the socio-economic situation of the country is taken into consideration and steps have been taken. One of the most basic examples in this regard is the question of agriculture and agricultural schools. After Abdülhamid II came to power, modernization, and agriculture education in the field of agriculture came to the agenda and a long-lasting first step was taken by entering an agricultural school facility in Halkalı. Agricultural Schools were not only limited to İstanbul, but also established in provinces. In this study, Hüdavendigar Agricultural School and Sample Farm opened in Bursa in line with the educational policies and agriculture understanding of the period of Abdülhamid II was discussed. In this context, detailed information about the opening process of the school, administrative and teaching staff, curriculum and courses, examinations, number of students, graduation, social status of the school and the farm were given. The Agricultural School in Bursa, along with the Halkalı and Selanik Agricultural Schools, was one of the three educational institutions in the Ottoman Empire where modern agriculture education was given. Subsequently, these schools continue to exist in the Constitutional Monarchy and the Republic of Turkey, the only school of its kind today maintained its historic mission of the agricultural school built Abdülhamid II period, has a unique place in the history of Turkish education.
AGRICULTURAL EDUCATION MOVE IN THE ABDULHAMID II PERIOD: HUDAVENDIGAR HAMİDİYE AGRICULTURAL PRACTICE SCHOOL AND SAMPLE FARM (1891-1909)